Shortening Accommodated by Thrust and Strike‐Slip Faults in the Ili Basin, Northern Tien Shan. Issue 7 (5th July 2019) - Grützner, C.; Campbell, G.; Walker, R.T.; Jackson, J.; Mackenzie, D.; Abdrakhmatov, K.; Mukambayev, A.
Abstract: The Tien Shan accommodates a significant portion of the India‐Eurasia N‐S convergence. In its northern part a zigzag pattern of mountain ranges bounds the western Ili Basin. The role of this basin in the overall shortening and the regional kinematics is not well understood. Geodetic data and instrumental seismicity are not sufficient to infer the role of individual faults and fault systems. We analyze GPS data and earthquake slip vectors and present the results of fault mapping based on remote sensing and field campaigns in the western Ili Basin. These observations indicate that E‐W thrust faults are active at the basin margins, and oblique and strike‐slip faults, both in the basin and in the Paleozoic rocks within the mountain ranges, have been active in the Late Quaternary. We propose a regional tectonic model in which the left‐lateral strike‐slip faults at the NW margin of the basin accommodate 3‐mm/year NE‐SW shear. Smaller right‐lateral oblique faults transfer the motion in between the left‐lateral faults, and also take up shortening by rotations about vertical axes. We see the onset of internal deformation within the Ili Basin, although it has a strong basement. Our kinematic model is consistent with geodetic data, earthquake seismology, historical, and prehistorical surface faulting, and describes the first‐order features of active deformation that can be observed in the northern Tien Shan. Our study illustrates the importance of combining these different data sets to understand the regional tectonics. Key Points: We investigated active faults in the western Ili Basin in the Tien Shan by remote sensing, field studies, earthquake seismology, and GPS data Large left‐lateral strike‐slip faults accommodate a NE‐SW shear component Oblique right‐lateral faults transfer deformation between large left‐lateral strike‐slip faults and accommodate shortening by rotation about vertical axes